Parental Support Strategies and Structural Challenges in Rural EFL Learning: A Qualitative Case Study in Jambi Province - Nurul Izzah Aulia; Urip Sulistiyo; Rosinta Norawati; Hadiyanto Hadiyanto; Mukhlash Abrar (Journal of Educational Sciences, 2026)
In rural EFL contexts, classroom instruction often provides the main exposure to English, making parental support an important factor in sustaining students’ learning beyond school. This study aimed to examine how rural parents perceive their role, what forms of support they provide, and what structural challenges they face in supporting their children’s English learning in a senior high school in Jambi Province, Indonesia. A qualitative case study design was employed. Four parents were selected through purposive sampling, and data were collected through individual semi-structured interviews conducted in Bahasa Indonesia. The data were analyzed thematically using the interactive model of data reduction, data display, and conclusion drawing. The findings revealed three main themes. First, parents viewed English as a practical life skill related to future education, employment, and social mobility. Second, parental support appeared in emotional, appraisal, instrumental, and informational forms, although parents had limited English proficiency. Third, parental involvement was shaped by limited English proficiency, time management challenges, financial challenges, and rural educational challenges. The study concludes that rural parents are adaptive learning partners and that schools should develop parent-engagement programs that do not require parents to master English.